Exploring Paulo Coelho’s The Alchemist from the Deconstructive Angle - Sharma, Bam Dev (Bon Voyage, 2024)
This research article explores The Alchemist by Paulo Coelho from the deconstructive angle. Based on the quest of exploration and adventure of the treasure by a shepherd, Santiago, this article tries to interpret the treasure hunt as the deconstructive signifiers. As the dominant signifier is the treasure hunt, the central idea of the novel is configured in the interpretation of the dream submerged with several signifying process connected with the treasure hunt. This signifying process, then, gets interlinked with some striking terms like journey, magician’s quest, dream, desert, and others. That is, the journey of the main character, Santiago is baffling, for it cannot reflect a set journey that is fixed in his mind, but a process of trial and error. Like the deconstructive labyrinthine connection, therefore, the signifiers’ fleeting course binds the journey as mere interpretation of the people in course of meeting for further perusal. Some of it is part of the dream which is, by nature fleeting. This, thus, projects a deconstructive angle connected just as an expansion of the meanings or multiple meanings in the lack of one concerted meaning. That being considered, the journey in Santiago’s dream reflects one conceptual image which invariably differs from the rest, like the deconstructive realm of interpretation. This is also analogical to the meaning being pushed aside in deconstructive angle: a subterfuge postponing of set meanings. This being the case, this article relies on interpretative analysis and qualitative approach of research corroborating ideas of the famous theorists like Jacque Derrida, and J. Miller, Mary Poovey and A. T. Nuyen. In addition, the textual interpretation and analysis are focused on some of the thematically significant words like dream, journey, and treasure, which help shape deconstructive lenses.